2018
DOI: 10.7759/cureus.2152
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-Induced Lactic Acidosis: A Case Study

Abstract: Metformin is the first line management for patients with Type 2 diabetes mellitus. Metformin-induced lactic acidosis (MALA) is a severe side effect of metformin in high doses. However, there have not been many reported cases of MALA. The threshold metformin concentration needed to induce lactic acidosis is still not fully understood. It is important for physicians to measure metformin levels upon admission in Type 2 diabetes patients who take metformin and present with suspected lactic acidosis. We present a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
3
0
1
Order By: Relevance
“…This is a case where a patient was being treated with the recommended Met dose and presented at the emergency unit and was diagnosed with AKI. PK analysis revealed that AKI might be caused by high plasma Met levels, consistent with previous reports that have demonstrated that Met overdose causes AKI [ 7 – 9 ]. Possible mechanism to cause AKI by Met is the decrement of mitochondrial adenosine triphosphate (ATP) by Met [ 10 ] since AKI can arise from mitochondrial ATP depletion [ 11 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is a case where a patient was being treated with the recommended Met dose and presented at the emergency unit and was diagnosed with AKI. PK analysis revealed that AKI might be caused by high plasma Met levels, consistent with previous reports that have demonstrated that Met overdose causes AKI [ 7 – 9 ]. Possible mechanism to cause AKI by Met is the decrement of mitochondrial adenosine triphosphate (ATP) by Met [ 10 ] since AKI can arise from mitochondrial ATP depletion [ 11 ].…”
Section: Discussionsupporting
confidence: 90%
“…This high Met concentration occurred in a patient who attempted suicide by taking 26,250 mg of Met (42.9 µg/mL at admission); this patient displayed acute tubular necrosis [ 7 ]. In the case a person without renal dysfunction overdosed on Met, he presented with high Met concentrations and consequently with AKI [ 9 ]. These results suggest that high Met concentrations possibly cause AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, Metformin ingestion should always be considered in the differential diagnoses of any patient with metabolic acidosis and high lactate level. (22,23). Activated charcoal should be considered in patients who present soon after ingestion, provided that there are no contraindications (10,26).…”
Section: Discussionmentioning
confidence: 99%
“…However, metformin-induced metabolic acidosis, which is a serious complication with a mortality rate of 50%, may rarely occur. This complication is known to be associated with lactic acid elevation [3].…”
Section: Introductionmentioning
confidence: 99%